Evaluasi Sistem Pengolahan Limbah Bahan Berbahaya dan Beracun (B3) pada Perusahaan Karet (Studi Kasus: PT. X di Kalimantan Barat) - Ningrum, Islamiati Kusuma; Asbanu, Govira Christiadora; Desmaiani, Herda (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
One of the businesses in West Kalimantan involved in the rubber industry is PT. X. This business converts raw rubber in the form of lumps and solid sheets into rubber sir, also known as semi-finished rubber. Apart from creating the intended products, PT. X also generates waste in the form of B3 waste from running the machinery that processes rubber. The purpose of this study is to assess, identify, and offer recommendations for the B3 waste management system of PT. X. Using a Likert scale, the evaluation is conducted in accordance with Permen LHK No. 6 of 2021 and PP No. 22 of 2021. Recommendations for B3 waste management are made by taking into account the evaluation results that do not comply with applicable regulations, According to study results, the reduction criteria's evaluation scores were in the 55.56% bracket, which is considered to be fairly good,; the criteria for containers and packaging were 95.24% category 'Very Good'; the criteria for storage was 86.67% category 'Very Good'; the criteria for storage buildings was 94% category 'Very Good'; the criteria for waste labels was 100% category 'Very Good'; and the criteria for transportation was 100% category 'Very Good'. Based on the findings of the evaluation, suggestions are given for the management of B3 waste at PT.X, starting with the phases of reduction, storage, and transportation.